Komik Interaktif Sains Bilingual sebagai Sarana Kreatif Belajar Bahasa dan Sains di Yayasan Kampus Diakoneia Modern Bekasi - Yulika Rahmawati; Rifka Aisyah Rokhmah; Elvira Dwi Sanpratina; Veronika Veronika; Indica Yona Okyranida (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2021)
Background: Children at the Modern Deaconeia Campus Foundation generally come from marginal vulnerable, vulnerable to taking to the streets because the child experiences discomfort in the house with his family due to violence, neglect, and exploitation. Still low interest in learning and reading makes the low knowledge that children have. The program aims to increase interest in learning science and English for street children and the underprivileged in the environment of the Modern Deaconeia Campus Foundation for science and English learning facilities that are fun for them. Method: The implementation of community service program will be held at the Foundation of The Modern Diakoneia Campus of Jalan Rawa Dolar No.29, RT.01 / RW.05, Jatiranggon Village, Jatisampurna District, Bekasi City, West Java which will be held for 4 months with a total of 36 participants. In the implementation of PKM Community Service is done blended by combining online and offline activities. Result: Activities take place well by responding to the increasing interest of children in reading and their science skills increase. Conclusion: Bilingual science comics have a positive impact on students in terms of increasing interest in learning and reading.